Fish diversity and Socio-economic Condition of Fishermen at the Halti Beel in Natore District, Bangladesh (Bangladesh Journal of Zoology, 2022)
This study was conducted to investigate the fish diversity and livelihood condition of fishermen community at Dangapara village of Halti beel, Singra, Natore. The socio-economic data were collected from 50 randomly selected fishermen using questionnaire survey between July and October 2019. In this study, a total of 43 fish species were recorded under seven orders, 20 families and 32 genera. Majority of fishermen were illiterate (44%), about 28% fishermen could sign only, 24% and 4% fishermen were completed primary and secondary education, respectively. Among them 79% were Muslims and 21% were Hindus. The majority of fishermen had mud house with straw and tin roof while 56% household used tin roof, 34% household used tin shed with tin roof, only 10% household used straw. Fishermen annual income was between 30001 to 40000 BDT. About 66% household had kacha toilets, 30% household had semi paka toilets, only 4% household had no sanitary facilities. The most of the households (78%) were used electricity as their energy source. The majority of fishermen (64%) were received health service from village doctors. About 44% fishermen was directly engaged in fishing as their main occupation while 26% and 24% fishermen were engaged in labor and agriculture activities, only 8% fishermen was engaged in other professions.Bangladesh J. Zool. 50 (1): 37-49, 2022